Evaluation Of 28nm 10 Bit Adc Using Ramp And Sinusoidal Histogram Methodologies - Wan Ismail, Wan Mohd Fahmi (2015)
ADC production testing has become more challenging due to more stringent test procedure for new generation of ADC. The trend for silicon cost is going down while the cost of test is going up. Therefore, to reduce the cost of test and preserve the test accuracy is essential for high volume testing in production. This research is conducted for accurate ADC testing using histogram methodologies. Histogram methodology is the most common test procedure used in high volume production testing. In the past there were a lot of studies on testing the ADC but there were no emphasizing on various histogram methodologies for high volume testing. This research objective is to develop test solutions for 28nm 10 bit ADC using histogram methodologies. The outcome from this research has clearly shows that the test program that has been developed is able to segregate the good and bad devices. 98.18% of the devices are able to pass the ADC testing while remaining 1.82% fail the ADC test. It was found that Ramp Histogram and Sinusoidal Histogram method has achieved this research objective as both methodologies shows similar result based on comparison that has been made. It was known that accurate ADC testing requires large sample size. This research found that multi-site testing was able to compensate the drawback in histogram methodologies. The result shows that multi-site testing is 63.72% more efficient in term of ADC testing time.